Earthworm diversity in Rio Grande do Sul, Brazil - Steffen, Gerusa Pauli Kist; Steffen, Ricardo Bemfica; Bartz, Marie Luise Carolina; James, Samuel Wooster; Jacques, Rodrigo Josemar Seminotti; Brown, George Gardner; Antoniolli, Zaida Inês (Zootaxa, 2018)
The knowledge regarding earthworm species richness in subtropical Brazil is limited, particularly in the state of Rio Grande do Sul (RS), where only a few sites have been sampled. In this study we assessed earthworm richness in different ecosystems of RS, prioritizing un-sampled regions. Fifteen ecosystems, including native vegetation and other ecosystems with variable levels of disturbance were sampled in 30 counties in RS, totaling 77 sampling points, mainly in the Pampa biome. Qualitative sampling was performed by handsorting soil monoliths and fixing the earthworms in 4% formalin solution. Species identification was based on morphological characters, and species richness and Shannon (H) and McIntosh (U) diversity indices were calculated for each ecosystem. Twenty-one earthworm species were identified, belonging to seven families: Glossoscolecidae (8), Rhinodrilidae (2), Ocnerodrilidae (4), Megascolecidae (4), Acanthodrilidae (1), Lumbricidae (1) and Criodrilidae (1). From these, ten are new species belonging to the genera: Glossoscolex (6), Fimoscolex (1), Kerriona (1), Eukerria (1), and one aquatic species of the Criodrilidae family, belonging to a new genus. Most of the native species (Urobenus brasiliensis, Fimoscolex n.sp.1 and the Glossoscolex spp.) predominated in ecosystems little altered by human activity, while exotic (Amynthas gracilis, Amynthas rodericensis, Metaphire californica, Aporrectodea trapezoides) and peregrine species (Pontoscolex corethrurus) predominated in areas with more human disturbance. Native ecosystems with lower disturbance, particularly forests and native pastures had higher diversity than disturbed sites. This is the first record of A. rodericencis for Brazil and most sites represent new collection records for the known species in RS.